2016
DOI: 10.5194/bg-13-1901-2016
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of the Mediterranean trophic regimes from ocean color satellites

Abstract: Abstract. D'Ortenzio and Ribera d'Alcalà (2009, DR09hereafter) divided the Mediterranean Sea into "bioregions" based on the climatological seasonality (phenology) of phytoplankton. Here we investigate the interannual variability of this bioregionalization. Using 16 years of available ocean color observations (i.e., SeaWiFS and MODIS), we analyzed the spatial distribution of the DR09 trophic regimes on an annual basis. Additionally, we identified new trophic regimes, exhibiting seasonal cycles of phytoplankton … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
105
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
1

Relationship

8
0

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 64 publications
15
105
0
Order By: Relevance
“…This pattern is confirmed by the phenology of the underlying phytoplankton dynamics that varies from ultra-oligotrophic regimes in the eastern basin to bloom regimes in the northwestern basin (D'Ortenzio et al, 2009). An extended study on the geographical distribution of these regimes -related to the Mediterranean bio-regionshas revealed significant changes at regional scales during the last decades (Mayot et al, 2016). Indeed, the seasonal cycle of biomass concentration turns out to be a reliable indicator of the response of pelagic ecosystems to external perturbations (Siokou-Frangou et al, 2010).…”
Section: Context Of the Cruisementioning
confidence: 99%
“…This pattern is confirmed by the phenology of the underlying phytoplankton dynamics that varies from ultra-oligotrophic regimes in the eastern basin to bloom regimes in the northwestern basin (D'Ortenzio et al, 2009). An extended study on the geographical distribution of these regimes -related to the Mediterranean bio-regionshas revealed significant changes at regional scales during the last decades (Mayot et al, 2016). Indeed, the seasonal cycle of biomass concentration turns out to be a reliable indicator of the response of pelagic ecosystems to external perturbations (Siokou-Frangou et al, 2010).…”
Section: Context Of the Cruisementioning
confidence: 99%
“…The metrics CHL_Year, CHL_March and CHL_Max refer to the yearly average [Chl a], the March average [Chl a] and the [Chl a] annual maximum, respectively. CHL_March has been defined here because previous studies demonstrated that the Mediterranean Sea trophic situation is highly variable in March, spatially and interannually ranging from oligotrophy to bloom conditions (D'Ortenzio et al, 2009(D'Ortenzio et al, , 2003Mayot et al, 2016). The bloom onset was defined as the date of the maximum growth rate.…”
Section: Phenological Metricsmentioning
confidence: 99%
“…Comparing surface chlorophyll a measured by the CZCS (Coastal Zone Color Scanner;1979-1985 and SeaWiFS (Sea-viewing Wide Field-of-view Sensor;-2000, D'Ortenzio et al (2003) observed just a slight difference in the timing of main bloom events and, during the SeaWiFS period, a recurrent and large patch of [Chl a]. More recently, Mayot et al (2016) studied interannual variability in phytoplankton phenology in the Mediterranean Sea. The authors showed that phytoplankton phenology is extremely dynamic in the north Ionian Sea with significant changes in the annual cycle of surface chlorophyll a concentration from year to year.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing surface chlorophyll-a measured by the CZCS (1979CZCS ( -1985 and SeaWiFS (1997SeaWiFS ( -2000 ocean color sensors, D 'Ortenzio et al (2003) observed just a slight difference in the timing of main bloom events and, during the SeaWiFS period, a recurrent and large patch of [Chl-a]. More recently, Mayot et al (2016) showed that phytoplankton phenology is extremely dynamic in the North Ionian Sea with significant 15 changes in the annual cycle of surface chlorophyll-a concentration from year to year. However, the authors did not explain this interannual variability.…”
Section: Introductionmentioning
confidence: 99%
“…Then, daily averages were computed 20 and the net heat flux was calculated as the sum of the four air-sea fluxes components. The surface buoyancy flux per unit area was computed according to Anderson et al (1996), with coefficients proposed by Gacic et al (2002) CHL_March has been defined here because previous studies demonstrated that in the Mediterranean Sea trophic situation is highly variable in March spatially and interannually ranging from oligotrophy to bloom conditions (D'Ortenzio et al, 2009;D'Ortenzio et al, 2003;Mayot et al, 2016). The bloom initiation was defined as the date of the maximum growth rate.…”
Section: Introductionmentioning
confidence: 99%